إشكالية تعارض التسويق العصبي مع أخلاقيات من وجهة نظر المستهلك الجزائري - شعباني, مجيد; جديان, منال (جامعة الوادي- University of Eloued, 2017)
This research work is, on the one hand, a study about the problematic of contradicting the commercial practice (marketing’s practice) with the ethics as a point of view.i.e., in agreement with the researchers’ opinions and, on the other hand, according to the Algerian customer’s view considered as exposed to the neuromarketing’s practices from different regions that are all the inhabitants of the globe. The Neuromarketing’s practices are based on two tenets:(1) the identification of the target individuals’ ideas and perceptions by displaying some advertisements and images in front of certain individuals and filming the target individuals’ brain activities by sophisticated medical devices. This practice is done for the purpose of evaluating the enterprises which have conducted studies for their successfulimage andtesting their new products. (2) The activation of the brain site that directs the individuals through purchasing by means of communication that addresses the subconscious.
The Problematic of the Neuromarketing’s Contradiction with the Ethics according to the Algerian Customer’s Perspective
مقال
Keywords: Neuromarketing, Neuroscience, the unconscious, perception, Ethics.